1999
DOI: 10.1080/10903129908958933
|View full text |Cite
|
Sign up to set email alerts
|

Are heroin overdose deaths related to patient release after prehospital treatment with naloxone?

Abstract: Giving naloxone to heroin overdoses in the field and then allowing the patients to sign out AMA resulted in no death in the one-year period studied. This study did not evaluate for return visits by paramedics nor whether patients were later taken to hospitals by private vehicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 4 publications
0
37
0
Order By: Relevance
“…Robust evidence has now established that harm reducing interventions like overdose prevention, better syringe access, and drug treatment do provide real health benefits to the IDU population and the broader community, including considerable savings in the use of public resources. 10,12,50,51 Side effects of naloxone administration and danger of overdose reversal have been found to be minimal, 19 and providers_ concerns about proper care can be addressed by bundling distribution programs with resuscitation and monitoring techniques. 8,13,19,41 A nasal delivery system can assuage provider anxiety about improper injection of the agent.…”
Section: Physicians Prescribing Naloxone To Reverse Opiate Overdosementioning
confidence: 99%
See 2 more Smart Citations
“…Robust evidence has now established that harm reducing interventions like overdose prevention, better syringe access, and drug treatment do provide real health benefits to the IDU population and the broader community, including considerable savings in the use of public resources. 10,12,50,51 Side effects of naloxone administration and danger of overdose reversal have been found to be minimal, 19 and providers_ concerns about proper care can be addressed by bundling distribution programs with resuscitation and monitoring techniques. 8,13,19,41 A nasal delivery system can assuage provider anxiety about improper injection of the agent.…”
Section: Physicians Prescribing Naloxone To Reverse Opiate Overdosementioning
confidence: 99%
“…10,12,50,51 Side effects of naloxone administration and danger of overdose reversal have been found to be minimal, 19 and providers_ concerns about proper care can be addressed by bundling distribution programs with resuscitation and monitoring techniques. 8,13,19,41 A nasal delivery system can assuage provider anxiety about improper injection of the agent. 13,35 Communicating this evidence to physicians is the most immediate step to address the lack of knowledge and sense of treatment futility our survey highlights.…”
Section: Physicians Prescribing Naloxone To Reverse Opiate Overdosementioning
confidence: 99%
See 1 more Smart Citation
“…Within 0 to 2 days of naloxone administration, the proportion of patients was 0 percent in three studies [71][72][73] (n=317, 552, and 998), one study 74 reporting one death (0.49% [1/205]), and one study 70 reporting 14 deaths (0.6% [14/2241]): three attributed to likely rebound overdose (0.13%), ten to new overdose, and one to a natural death. The final study reported one case of a life-threatening adverse event (1.2% [1/84]).…”
Section: Detailed Synthesismentioning
confidence: 99%
“…Although six studies reported low rates (0 to 1.2%) of death or serious adverse events among patients who received naloxone for opioid overdose and were not transported to a health care facility, [69][70][71][72][73][74] there was no comparison group of patients who were transported, and the studies provided limited details regarding the characteristics of the nontransported patients. This makes interpretation of findings difficult, as patients who refuse transport or are assessed as not requiring transport are likely to be at lower risk of opioid overdose-related complications than patients who are transported.…”
Section: Key Findings and Strength Of Evidencementioning
confidence: 99%